Morphological and genetic identification of Halophila species and a new distribution record of Halophila nipponica at the Tanjung Adang Laut shoal, Johor, Malaysia - Che Alias, Muhammad Afif; Zakaria, Muta Harah; Ramaiya, Shiamala Devi; Esa, Yuzine; Ab. Ghani, Nurul Izza; Bujang, Japar Sidik (Public Library of Science, 2024)
The Halophila species exhibit complex characteristics due to their high degree of variation across different bioregions. This study delves into the intricate characteristics of Halophila species in the Tanjung Adang Laut shoal, Johor, Malaysia, and offers valuable insights through morphological and genetic evidence. Employing internal transcribed sequences (ITS), we investigated the phylogeny of Halophila species, revealing distinct clades for H. ovalis, H. major, H. spinulosa, and the newly recorded H. nipponica. Notably, H. nipponica from the Tanjung Adang Laut shoal formed a conspecific relationship with its counterparts from Japan and Korea (98.3-98.5% similarity; 5-11 bp differences). Morphologically, distinguishing features, including the ratio of the half-lamina width (1:4.76-6.13 mm) and crossvein count (4-7 pairs), supported the identification of H. nipponica. Genetic distance analyses revealed differences between H. nipponica, H. ovalis, and H. major, indicating haplotype diversity. Geographical variations were evident, as H. nipponica presented unique haplotypes (H24) in its clade. The 47 haplotypes network identified significant mutation sites, providing a comprehensive understanding of genetic and morphological distinctions. In conclusion, this study highlights the intricate characteristics and phylogeny of Halophila species in the Tanjung Adang Laut shoal, Johor, and provides valuable insights into their genetic and morphological diversity.